Alterations in local activity and functional connectivity in patients with postherpetic neuralgia after short-term spinal cord stimulation - Fan, Xiaochong; Ren, Huan; Bu, Chunxiao; Lu, Zhongyuan; Wei, Yarui; Xu, Fuxing; Fu, Lijun; Ma, Letian; Kong, Cunlong; Wang, Tao; Zhang, Yong; Liu, Qingying; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective: This study aimed to investigate the effect of therapy with peripheral nerve stimulation (PNS) and pulsed radiofrequency (PRF) combined or PNS and PRF separately in patients with herpes zoster ophthalmicus (HZO). Methods: This cohort study included 106 cases of HZO. Three groups were identified according to the type of treatment received: combination therapy ( PNS + PRF ) ( n = 38 ), PRF ( n = 37 ), and PNS ( n = 31 ). The observations at 0, 1, 2, 4 weeks; 3 and 6 months; and 1 and 2 years after the operation were extracted and analyzed. Observations at each follow-up included baseline characteristics, NRS and the Pittsburgh Sleep Quality Index (PSQI), concomitant pain medication usage, relapse rate and adverse events. Results: The postoperative NRS of all three groups were significantly lower than preoperative scores. The PSQI of the three groups was significantly improved postoperatively, and the concomitant pain medication gradually decreased. Regarding long-term efficacy, the pain NRS and PSQI scores of the PNS + PRF and PNS groups were significantly lower than those of the PRF group (P<0.05), and the relapse rate of the PRF group was higher than that of the PNS + PRF and PNS groups (P<0.05). No significant difference was observed between the PNS+PRF group and the PNS group. Conclusion: Both PNS and PRF treatment of HZO can decrease the pain score, yielding no serious complications. The combination of PNS and PRF or PNS alone resulted in more significant pain relief than treatment with PRF alone. Thus, PNS therapy may be a better treatment option for HZO.